Air pollution and endurance exercise: A systematic review of the potential effects on cardiopulmonary health - González Rojas, Sofía.; Yáñez Sepúlveda, Rodrigo.; Tuest, Marcelo; Sánchez Ureña, Braulio.; Trejos Montoya, José.; Olivares Arancibia, Jorge Eduardo.; López Gil, José Francisco.; Rojas Valverde, Daniel. (MDPI, 2025)
This systematic review aimed to analyze the implications of endurance exercise in environments with certain levels of air pollution. This study was developed on the basis of the consensus of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The present review is supported by articles containing the main databases PubMed, Elsevier, and Web of Science (WoS), including scientific articles published in the last 20 years. This study highlights that exposure to air pollution during endurance activities, such as cycling and outdoor running, significantly affects cardiopulmonary health. In conclusion, while physical exercise in environments with high air pollution presents significant risks to cardiopulmonary health, implementing preventive measures and adopting public policies are crucial to minimizing these impacts and promoting safe exercise practices. Likewise, on the basis of these results, it is possible to motivate the creation of safe and natural spaces for sports practice.
Keywords: Actividad motora; Contaminación; Actividad física; Cardiovascular; Environmental